Molecular Characterization, Gene Evolution, and Expression Analysis of the Fructose-1, 6-bisphosphate Aldolase (FBA) Gene Family in Wheat (Triticum aestivum L.) - Lv, Geng-Yin; Guo, Xiao-Guang; Xie, Li-Ping; Xie, Chang-Gen; Zhang, Xiao-Hong; Yang, Yuan; Xiao, Lei; Tang, Yu-Ying; Pan, Xing-Lai; Guo, Ai-Guang; Xu, Hong (Frontiers in Plant Science, 2017)
Fructose-1, 6-bisphosphate aldolase (FBA) is a key plant enzyme that is involved in glycolysis, gluconeogenesis, and the Calvin cycle. It plays significant roles in biotic and abiotic stress responses, as well as in regulating growth and development processes. In the present paper, 21 genes encoding TaFBA isoenzymes were identified, characterized, and categorized into three groups: class I chloroplast/plastid FBA (CpFBA), class I cytosol FBA (cFBA), and class II chloroplast/plastid FBA. By using a prediction online database and genomic PCR analysis of Chinese Spring nulli-tetrasomic lines, we have confirmed the chromosomal location of these genes in 12 chromosomes of four homologous groups. Sequence and genomic structure analysis revealed the high identity of the allelic TaFBA genes and the origin of different TaFBA genes. Numerous putative environment stimulus-responsive cis-elements have been identified in 1,500-bp regions of TaFBA gene promoters, of which the most abundant are the light-regulated elements (LREs). Phylogenetic reconstruction using the deduced protein sequence of 245 FBA genes indicated an independent evolutionary pathway for the class I and class II groups. Although earlier studies have indicated that class II FBA only occurs in prokaryote and fungi, our results have demonstrated that a few class II CpFBAs exist in wheat and other closely related species. Class I TaFBA was predicted to be tetramers and class II to be dimers. Gene expression analysis based on microarray and transcriptome databases suggested the distinct role of TaFBAs in different tissues and developmental stages. The TaFBA 4-9 genes were highly expressed in leaves and might play important roles in wheat development. The differential expression patterns of the TaFBA genes in light/dark and a few abiotic stress conditions were also analyzed. The results suggested that LRE cis-elements of TaFBA gene promoters were not directly related to light responses. Most TaFBA genes had higher expression levels in the roots than in the shoots when under various stresses. Class I cytosol TaFBA genes, particularly TaFBA10/12/18 and TaFBA13/16, and three class II TaFBA genes are involved in responses to various abiotic stresses. Class I CpFBA genes in wheat are apparently sensitive to different stress conditions.